ANTHOCYANIN AS NATURAL COLORANT: A REVIEW - Winda Nurtiana (Food ScienTech Journal, 2019)
On this era, people very concern to their food. The first sensory quality which is seen to choose the food are the color. However, during food processing is often occurred the color degradation, so the colorant is added to the food. Today, natural colorant is consumer’s selection because it has functional function. One of natural colorant is anthocyanin. Anthocyanin gives red, blue, and purple color. Anthocyanin has different types, it is depended to sugar and hydroxyl which bounded into structure. The types are pelargonidin, malvidin, cyanidin, delphinidin, petunidin, and peonidin. This pigment is stable on acid condition, away from light and oxygen, cold temperature, and away from polyphenol oxidase enzyme. Beside as colorant, anthocyanin also act as antioxidant because the structure is very reactive. The consequences of having antioxidant activity, anthocyanin can prevent cardiovascular disease, cholesterol, atherosclerosis, or colon cancer by blocking fat oxidation and DNA mutation. Anthocyanin source is very broad like from flowers, fruits, tubers, or fruit peels.